1989
DOI: 10.1002/jat.2550090603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the developmental toxicity of five compounds with the frog embryo teratogenesis assay: Xenopus (FETAX) and a metabolic activation system

Abstract: The potential teratogenic hazard of five compounds was evaluated using the Frog Embryo Teratogenesis Assay--Xenopus (FETAX) and a metabolic activation system. Embryos of the South African clawed frog, Xenopus laevis, were exposed to (i) three compounds suspected to be proteratogenic in mammalian test systems--[2-acetylaminofluorene (2-AAF), rifampicin (RA) and benzo[a]pyrene (BP)] for 96 h; (ii) one compound unaffected by mixed-functional oxidase (MFO) metabolism--ZnSO4; (iii) one compound thought to be inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…It is interesting to note that growth-inhibiting potential in the present study directly follows the trend in teratogenic potential. The same similarity in trends was identified during validation of FETAX with X. laevis (Dawson and Bantle, 1987;Dawson et al, 1989;Fort et al, 1989Fort et al, , 1990Fort et al, , 1992Bantle et al, 1990;Sunderman et al, 1991;Dresser et al, 1992).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is interesting to note that growth-inhibiting potential in the present study directly follows the trend in teratogenic potential. The same similarity in trends was identified during validation of FETAX with X. laevis (Dawson and Bantle, 1987;Dawson et al, 1989;Fort et al, 1989Fort et al, , 1990Fort et al, , 1992Bantle et al, 1990;Sunderman et al, 1991;Dresser et al, 1992).…”
Section: Discussionsupporting
confidence: 56%
“…The Frog Embryo Teratogenesis Assay -Xenopus (FETAX) model was originally developed by Dumont et al (1983), standardized via the American Society of Testing and Materials (ASTM, 1998) and validated as an alternative developmental toxicity screening test to determine the relative developmental toxicity hazard of chemical agents and complex mixtures (Dawson et al, 1989;Fort et al, 1989;Bantle et al, 1990Sunderman et al, 1991;Dresser et al, 1992;Fort et al, 1992Morgan et al, 1996). Interlaboratory validation studies have strongly supported the FETAX as a promising alternative prescreening test system capable of minimizing the cost and time restraints associated with the use of conventional mammalian test organisms, as well as the number of mammalian specimens used in developmental toxicity testing (Bantle et al, 1994a(Bantle et al, ,b, 1996(Bantle et al, , 1999Fort et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In all experiments, the concentration of the solvent did not exceed 1% (v/v), per ASTM (2002) guidelines. These concentrations have been found not to cause any adverse effects in FETAX (Fort et al 1989). Solvent controls did not have significant effects on normal Xenopus development (i.e., at least 90% of controls survived without deformities throughout the duration of the test).…”
Section: Methodsmentioning
confidence: 93%
“…Specific aliquots of the Aroclor 1254-induced microsomes were pretreated with carbon monoxide (CO) to selectively modulate mixed function oxidase (MFO) activity. Inhibition with CO was achieved by chemically reducing 3 Teratogenic Index = LC50/EC50 (malformation). 4 Minimum concentration to inhibit growth determined using ANOVA -Dunnett's Test, P < 0.05.…”
Section: Fetaxmentioning
confidence: 99%
“…Endpoints measured include mortality, malformation, and growth. Validation studies have shown FETAX to have value in screening for chemical teratogens, determining teratogenic interactions, evaluating the developmental toxicity of complex environmental mixtures, and developing structure-activity relationships [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%